The Effectiveness of Vocal Learning in Visually Impaired Students Using Audio Visual Media and Picture Learning at SLB Negeri 1 Pemalang - Kamal, Adella Clarisca (Riwayat: Educational Journal of History and Humanities, 2025)
This study examines the effectiveness of vocal learning in students with disabilities using audiovisual media and picture learning in SLBN 1 Pemalang. Students with disabilities experience difficulties in conventional vocal learning due to cognitive limitations and the ability to understand abstract concepts such as pitch, rhythm, and lyrics. Traditional learning methods that rely on verbal instruction have proven to be less effective, resulting in low student participation in music learning This research integrates audiovisual media to stimulate hearing and vision simultaneously in understanding tone and rhythm, as well as picture learning that utilizes concrete images to facilitate the memorization of lyrics. The combination of the two media creates multisensory learning that is in accordance with the learning characteristics of students with disabilities who are responsive to visual stimuli. The research contribution is the development of an inclusive vocal learning model for students with special needs in exceptional schools.